Videogame and Thai Child’s Unwanted Behaviors - Phetcharaburanin, Prisana (Journal of Advanced Development in Engineering and Science, 2023)
Videogames have more important roles in the last few years and also have more problems from that role but there are only two problems that become talk of the town today, child?s imitation and addiction. These problems are not only reason from videogames but also from many factors such as family, environment and themself. Throwing and blaming videogame may not answer the problem. Only way to solve the problem is cooperation, everybody should pay attention and solve the problem together. Parent should set a rule about playing videogame and manage to put the videogame?s console in the proper position. Community should take care of their children by verifying their game center for suitable playing time. Government should enforce the law seriously and start rating system for videogame.